2016
DOI: 10.1017/s1471068416000351
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Learning of Answer Set Programs from Context Dependent Examples

Abstract: In recent years, several frameworks and systems have been proposed that extend Inductive Logic Programming (ILP) to the Answer Set Programming (ASP) paradigm. In ILP, examples must all be explained by a hypothesis together with a given background knowledge. In existing systems, the background knowledge is the same for all examples; however, examples may be context-dependent. This means that some examples should be explained in the context of some information, whereas others should be explained in different con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 15 publications
(35 reference statements)
0
51
0
Order By: Relevance
“…Note that the scalability results purely depend on the open-source prototype tool 7 used to support the specification synthesis. This could be significantly improved by deploying learning techniques for context-dependent learning [32], and distributed reasoning [34].…”
Section: Discussionmentioning
confidence: 99%
“…Note that the scalability results purely depend on the open-source prototype tool 7 used to support the specification synthesis. This could be significantly improved by deploying learning techniques for context-dependent learning [32], and distributed reasoning [34].…”
Section: Discussionmentioning
confidence: 99%
“…In [24], we showed that context-dependent examples could be used to simplify the encoding of certain tasks, by splitting the background knowledge into contexts that were only relevant to particular examples. Although any I L P …”
Section: Definition 9 a Context-dependent Learning From Ordered Answmentioning
confidence: 99%
“…Consequently, the scope of ILP has recently been extended to learning answer set programs from examples of partial solutions of a given problem, with the intention being to provide algorithms that support automated learning of complex declarative knowledge. Learning ASP programs allows us to learn a variety of declarative non-monotonic, common-sense theories, including for instance Event Calculus [20] theories [21] and theories for scheduling problems and agents' preference models, both from real user data [22] and from synthetic data [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations